Korelasi Tingkat Kebugaran Jasmani Terhadap Prestasi Belajar Mahasiswa Prodi PGSD Angkatan 2023 Universitas Muhammadiyah Tasikmalaya - Puteri Dhiya Nabilah; Fani Sri Aprilia; Fika Nurzakia Rahmah; Listhia Aulia Rahmah; Silvi Damayanti; Rahmat Permana (Indonesian Publication Center, 2024)
This study aimed to determine the relationship between physical fitness levels and academic achievement among PGSD students of the 2023 cohort at Universitas Muhammadiyah Tasikmalaya. The research employed a quantitative descriptive design with a correlational approach. The subjects consisted of 64 students, comprising 12 male and 52 female students. The instruments used included a physical fitness test to measure fitness levels and the Grade Point Average (GPA) to assess academic achievement. Data were collected through questionnaires and analyzed statistically. The analysis revealed that physical fitness was not a primary factor influencing students' academic achievement. The correlation coefficient (r) was -0.638, which was lower than the critical value (rt) of 0.526 at a 5% significance level, indicating no significant relationship between physical fitness and academic achievement. The coefficient of determination (r square) was 0.007 or 0.7%, suggesting that only 0.7% of the variation in academic achievement could be explained by physical fitness levels, while 99.3% was influenced by other factors such as motivation, talent, interest, and family environment. Thus, this study concludes that psychological and social factors play a more dominant role in determining students' academic success compared to physical fitness levels.